PERGESERAN NILAI HAK WARIS TERHADAP ANAK LUAR KAWIN DIAKUI (Studi Kasus Putusan Nomor 239/Pdt.G/2015/PN.JKT.PST) - Vidya Pradipta; Imelda Martinelli (Jurnal Hukum Adigama, 2018)
Illegitimate children that has been acknowledged are recognized as heirs who do not belong to the heirs class and cannot stand on their own but rather, they attach themselves to other heirs class. According to article 863 of the civil code law, outsiders are admitted to inheritance along with first heirs class is entitled to inherit 1/3 of those who should have been granted if they were legitimate children. In this case study, outsiders are recognized to have equal share of the estate with their legitimate children, indicating a distinction between applicable legislation and the development of values living in the community. The problem in this paper is how the shift in the value of inheritance rights to illegitimate children that has been acknowledged. The research method used is normative law research method, which is analyzed deductively. The results of the writing illustrate that there is a shift in the value of inheritance rights to illegitimate children that has been acknowledged where an illegitimate child that has been acknowledged is now recognized ‘equal’ as a legitimate child supported by argumentum per analogiam which analogies adopted child and the illegitimate child that has been acknowledged in terms of inheritance, three general precepts by Radbruch that prioritizes justice by observing the principle of fair equality of opportunity as long as it provides benefits and no harm to others, the theory of the legal system which not only refers to the substance of the law, but also see the culture or legal culture.